Male Reproductive Traits Display Increased Phenotypic Variation in Response to Resource Quality and Parental Provisioning in a Tropical Rainforest Dung Beetle, Onthophagus c.f. babirussa - Sean Yap; Kai Xin Toh; Nalini Puniamoorthy (Ecology and Evolution)
ABSTRACT Reproductive traits that mediate differential fitness associated with mate acquisition and fertilisation success are often strongly linked to the overall condition. We investigated the effects of resource quality and parental provisioning in the phenotypic expression of sexual and non‐sexual traits in a rainforest dung beetle, Onthophagus c.f. babirussa (Eschscholtz, 1822) from Singapore. F1 individuals were reared from wild‐caught beetles and paired up to produce offspring (F2), and F2 larvae from the same F1 parents were reared on two dung substrates (herbivore and omnivore) in a full‐sib design. Sexual traits displayed greater phenotypic variation in response to dung resource quality, with the precopulatory trait (horn length) responding more than the postcopulatory trait (testes weight). Notably, genotype‐by‐environment interactions between parental lines (genotype) and dung type (environment) affected male body size and horn length only, suggesting sex‐specific variance in plasticity associated with sexually selected precopulatory traits. Dung type had significant effects on all measured traits. Offspring that were provisioned higher quality resource (omnivore dung) had larger absolute and relative trait values. Parental lines only significantly affected female body size but none of the male traits, suggesting an important role of environment and resource partitioning in determining precopulatory success of male offspring. Parental provisioning of larval resource varied with resource quality and brood sequence. Parents provisioned more dung when herbivore dung was presented than when they were given omnivore dung and provisioned more dung for their earlier broods when using herbivore dung but not omnivore dung. This suggests a trade‐off between early offspring fitness and resource quality. We tested directly for genotype‐by‐environment (G × E) interactions in the expression of several morphological traits relevant to dung beetle fitness and documented that offspring with similar phenotypes may result from completely different parental resource allocation strategies. We discuss the importance of studying parental investment on trait variation and its implications on dung beetle ecology.